Does organizational citizenship behavior predict organizational commitment of employees in higher educational institutions? - Nguyen, Phuong Ngoc-Duy; Tran, Vi Dieu; Le, Dong Nguyen-Thanh (Frontiers in Education, 2022)
Many studies have been conducted in organizations on the topics of organizational commitment and organizational citizenship behavior (OCB). However, there is a shortage of these topics in higher education institutions as well as in the Asian context. Therefore, this article attempts to fill this literature gap. The study focuses to examine the influence of organizational citizenship behavior on organizational commitment in the higher education sector in Vietnam. It analyses in separate the effect of OCB’s components on three aspects of organizational commitment: affective commitment, normative commitment, and continuance commitment. A self-administered survey was collected from 301 employees who work for 21 higher education institutions in Ho Chi Minh City, Vietnam, and the structural equation analysis by using Smart PLS-SEM. The results support OCB components as helping, sportsmanship, loyalty, individual initiative, compliance, civic virtue, self-development effect on organizational commitment. Furthermore, the helping factor shows the strongest effect on organizational commitment. The research also found that there is a difference in terms of organizational commitment between groups of respondents based on age and educational level. However, the research addressed Ho Chi Minh City universities only, thus future research could broaden the sample size to vocational colleges as well as other Asian contexts. Theoretical contributions, practical implications, and future research directions are discussed.